3‐4: Ultra‐wide Color Gamut OLED Display using a Deep‐red Phosphorescent Device with High Efficiency, Long Life, Thermal Stability, and Absolute BT.2020 Red Chromaticity. Issue 1 (2nd June 2017) - Hosoumi, Shunsuke; Yamaguchi, Tomoya; Inoue, Hideko; Nomura, Shiho; Yamaoka, Ryohei; Sasaki, Toshiki; Seo, Satoshi
Abstract : We developed a deep‐red phosphorescent organic light‐emitting diode (OLED) with (x, y) chromaticity coordinates of (0.709, 0.290), high external quantum efficiency of 27.4%, and higher stability than a conventional red OLED. This device realizes an OLED display with a color‐gamut ratio of 101% to the BT.2020 standard.